2020
DOI: 10.1038/s41419-020-03020-9
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular amyloid toxicity induces oxytosis/ferroptosis regulated cell death

Abstract: Amyloid beta (Aβ) accumulates within neurons in the brains of early stage Alzheimer’s disease (AD) patients. However, the mechanism underlying its toxicity remains unclear. Here, a triple omics approach was used to integrate transcriptomic, proteomic, and metabolomic data collected from a nerve cell model of the toxic intracellular aggregation of Aβ. It was found that intracellular Aβ induces profound changes in the omics landscape of nerve cells that are associated with a pro-inflammatory, metabolic reprogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 48 publications
1
44
0
Order By: Relevance
“…Past decades have seen a rapid increase in research on tumor ferroptosis. This is an iron-dependent cell death reliant on intracellular accumulation of reactive oxygen species (ROS), distinct from apoptosis and autophagy 8 . Dysregulation of iron metabolism is a risk factor for cancer and as well promotes tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Past decades have seen a rapid increase in research on tumor ferroptosis. This is an iron-dependent cell death reliant on intracellular accumulation of reactive oxygen species (ROS), distinct from apoptosis and autophagy 8 . Dysregulation of iron metabolism is a risk factor for cancer and as well promotes tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on ferroptosis in tumors are on the ascendancy. Ferroptosis is an iron-dependent cell death mode that is characterized by intracellular accumulation of reactive oxygen species (ROS), which is distinct from apoptosis and autophagy in morphology 8 . The main mechanism of ferroptosis is that, under the action of divalent iron or ester oxygenase, it catalyzes the unsaturated fatty acids highly expressed on the cell membrane to cause liposome peroxidation, thereby inducing cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, one study observed that a Gpx4 knockout mouse exhibited significant deficits in spatial learning and memory function, and markers related to ferroptosis, such as elevated lipid peroxidation, and augmented neuroinflammation were also detected ( Hambright et al, 2017 ). Some other studies also have found evidence in support for a connection between AD and ferroptosis, and Gpx4 could protect cortical neurons from oxidative stress and amyloid toxicity ( Zhang et al, 2018 ; Huang et al, 2020 ). However, whether ferroptosis is the cause or consequence of AD is still unclear.…”
Section: Discussionmentioning
confidence: 88%